The role of the requirements of Total Quality Environmental Management in promoting environmental sustainability-An Empirical Study in the Iraqi Drilling Company - داود فضيلة سلمان; سلمان هبة ناجي (Journal of Economics and Administrative Sciences, 2016)
Abstract quality issue is the only issue the interesting in recent years of the last century, but also came out of sync with the other issue is the issue of environment, Where they have become represent two sides of one currency, challenges faced by the world and raised by the environmental problems have made industrial organizations pay great attention to the environment by improving their environmental performance, and that’s where the oil industry is one of the most dangerous industries, influential and damaging to the environment due to the organizations move away from oil for adoption The application of EMS then a tool to improve environmental performance has been chosen sample of the Iraqi Drilling Company,This research seeks to evaluate the reality of environmental performance through the diagnosis and analysis of the gap between the environmental performance of the Iraqi Drilling Company and the levels of the application to the requirements of the international standard of ISO14001: 2004)) and the requirements of Total Quality Environmental Management and dimensions of environmental sustainability, and determine the most important causes of the gap and propose solutions and remedies possible to fill gap , Was chosen the Iraqi Drilling Company, one of the formations and the Ministry of Oil to be a sample of the current research has been the study of the environmental reality of the company through the use of the checklist, especially the requirements of the environmental management system according to standard ISO14001: 2004)) and the requirements of Total Quality Environmental Management Representative (commitment of Top management, customer focus, teamwork, continuous improvement), In addition to the checklist for the dimensions of the environmental sustainability of current research (to reduce pollution, preservation of human health, the rationalization of resource consumption, use of renewable energy), The present research out there that are seeking a serious doing Iraqi Drilling Company, represented by its management top and departments specialized in the field of the environment to improve their environmental performance, but it is under preparation & Auditing did not apply actual actions in reality because of different circumstances Perhaps the most prominent security and political situation degraded.